1996
DOI: 10.1074/jbc.271.10.5656
|View full text |Cite
|
Sign up to set email alerts
|

DNA Aggregation Induced by Polyamines and Cobalthexamine

Abstract: We have studied the precipitation of short DNA molecules by the polycations spermidine, spermine, and cobalthexamine. The addition of these cations to a DNA solution leads first to the precipitation of the DNA; further addition resolubilizes the DNA pellet. The multivalent salt concentration required for resolubilization is essentially independent of the DNA concentration (between 1 g/ml and 1 mg/ml) and of the monovalent cation concentration present in the DNA solution (up to 100 mM). The DNA aggregates are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
390
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(435 citation statements)
references
References 30 publications
43
390
1
1
Order By: Relevance
“…This agrees with previous work showing that a significant amount of spermine is required to precipitate DNA (13). Prior experiments using CoHex suggest that an even higher concentration is required to completely draw the DNA out of solution (19). It is interesting that the poly(rA):poly(rU) RNA condenses out of solution in the presence of small amounts of spermine, consistent with previous literature reports (15) and in contrast to our findings on the mixed-sequence duplex.…”
Section: Measurement Of Duplex Condensationsupporting
confidence: 91%
See 1 more Smart Citation
“…This agrees with previous work showing that a significant amount of spermine is required to precipitate DNA (13). Prior experiments using CoHex suggest that an even higher concentration is required to completely draw the DNA out of solution (19). It is interesting that the poly(rA):poly(rU) RNA condenses out of solution in the presence of small amounts of spermine, consistent with previous literature reports (15) and in contrast to our findings on the mixed-sequence duplex.…”
Section: Measurement Of Duplex Condensationsupporting
confidence: 91%
“…Previous studies of spermine-induced RNA condensation had a limited scope but showed that spermine can condense RNAs with nonphysiological sequences or under nonphysiological experimental conditions, e.g., long duplex poly(rA):poly(rU) (15), tRNA at nonphysiological pHs (16), and viral RNA in the complete absence of other salts (17). More extensive studies of DNA condensation by spermine showed that even small numbers of spermines condense both long and short, natural and synthetic DNA duplexes (18)(19)(20). Since spermine is such an effective condensing agent, it seems plausible that it could also condense RNA in cells.…”
Section: Introductionmentioning
confidence: 99%
“…This often results in the under-representation of the larger chromosomes. It has been reported that with DNA in solution, the concentration of NaCl affects the solubilization state of DNA in the presence of polyamines (31). We found an increase in chromosome yield and a decrease in debris when NaCl is excluded from the PAB buffer ( Fig.…”
Section: Discussionsupporting
confidence: 57%
“…According to the Manning condensation theory, a fraction of the cations condenses into the Bjerrum layer near the molecular surface [1]. If some of the ions specifically adsorb onto DNA, its surface could be almost fully neutralized [2] or even overcharged [3]. Far from its axis, DNA can be apprehended as a charged cylinder.…”
mentioning
confidence: 99%